Annabba as Cultural Pedagogy: Exploring Local Wisdom Values in Bugis-Makassar Wedding Traditions - Hajerah Kadir; Rosmini Rosmini (Ikatan Dosen Sains dan Teknologi Indonesia, 2025)
This study investigates the local wisdom values embedded in the Annabba tradition within the customary wedding ceremonies of the Bugis-Makassar community in Pajjukukang Village, Maros Regency, South Sulawesi, Indonesia. Amidst the growing influence of modernization, cultural erosion, and youth disinterest in indigenous practices, the urgency of preserving and revitalizing traditional values has intensified. The Annabba tradition, conducted after the formal marriage proposal (mappasidde), embodies not only symbolic rituals but also deeply held ethical principles that shape family relations and community life. This research aims to explore how such values are manifested, sustained, and can be optimized to strengthen cultural identity and social cohesion. Employing a qualitative ethnographic approach, the study collected data through participatory observation, in-depth interviews, and documentation involving 15 purposively selected informants, including traditional leaders, family members, and traditional practitioners. The findings reveal five central values: gotong royong (mutual cooperation), respect for ancestors, simplicity, siri’ (sense of honor), and social solidarity. These values are expressed through inclusive decision-making, symbolic food rituals, ancestral prayers, and the communal organization of ceremonial events. The novelty of this study lies in its focused ethnographic documentation of a specific and underexplored cultural tradition as well as its proposal to integrate these values into educational and cultural preservation frameworks. It concludes that Annabba functions not merely as a customary procedure but as a culturally rooted pedagogical model that contributes to character education, cultural sustainability, and community resilience. This research contributes to the field of education by demonstrating how local wisdom can serve as a foundation for culturally responsive pedagogy.